Changing epidemiology of methicillin-resistant Staphylococcus aureus in Iceland from 2000 to 2008: a challenge to current guidelines - Holzknecht, Barbara Juliane; Hardardottir, Hjordis; Haraldsson, Gunnsteinn; Westh, Henrik; Valsdottir, Freyja; Boye, Kit; Karlsson, Sigfus; Kristinsson, Karl Gustaf; Gudlaugsson, Olafur (Journal of Clinical Microbiology, 2011)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field The epidemiology of methicillin-resistant Staphylococcus aureus (MRSA) is continuously changing. Iceland has a low incidence of MRSA. A "search and destroy" policy (screening patients with defined risk factors and attempting eradication in carriers) has been implemented since 1991. Clinical and microbiological data of all MRSA patients from the years 2000 to 2008 were collected prospectively. Isolates were characterized by pulsed-field gel electrophoresis (PFGE), sequencing of the repeat region of the Staphylococcus protein A gene (spa typing), staphylococcal cassette chromosome mec (SCCmec) typing, and screening for the Panton-Valentine leukocidin (PVL) gene. Two hundred twenty-six infected (60%) or colonized (40%) individuals were detected (annual incidence 2.5 to 16/100,000). From 2000 to 2003, two health care-associated outbreaks dominated (spa types t037 and t2802), which were successfully controlled with extensive infection control measures. After 2004, an increasing number of community-associated (CA) cases without relation to the health care system occurred. A great variety of clones (40 PFGE types and 49 spa types) were found, reflecting an influx of MRSA from abroad. The USA300 and Southwest Pacific (SWP) clones were common. SCCmec type IV was most common (72%), and 38% of the isolates were PVL positive. The incidence of MRSA in Iceland has increased since 1999 but remains low and has been stable in the last years. The search and destroy policy was effective to control MRSA in the health care setting. However, MRSA in Iceland is now shifting into the community, challenging the current Icelandic guidelines, which are tailored to the health care system.